Analysis of Factors Affecting Bank Profitability with Total Assets Minimum 1 (One) Billion - Irawati; Nur Indriyani, Siwi (Krisnadwipayana International Journal of Management Studies, 2022)
This research was conducted to examine the effect of variable banking ratio, fundsinterest rate, interest spread, fee based income ratio and inefficiency ratio ofProfitability (ROA). Profitability is used to measure the effectiveness of managementbased on results generated from the loan repayment and investment. The ratio isimportant for the bank's profitability is Return On Assets (ROA). Financial ratios thataffect the ROA is the banking ratio, funds interest rate, interest spread, fee basedincome ratio and inefficiency ratio. The sampling technique used was purposivesampling with the criteria of commercial bank serving the financial statements. Theanalysis technique used is the classical assumption of the analysis, multipleregression analysis and hypothesis test with a level of significance of 8,841%. Theresults of the research simultaneously (test F) states that the banking ratio, fundsinterest rate, interest spread, fee based income ratio and inefficiency ratio jointlyaffect the profitability (ROA) of banks. While the results show that the correlationcoefficient between profitability (ROA) of banks with 5(five) independent variablesof 60,336%. And the result of research partially (t) states that the variable interestspread did not have a significant effect on profitability (ROA) of banks. And variablebanking ratio, funds interest rate, fee based income ratio and inefficiency ratiosignificant effect on profitability (ROA) of banks.